Absence of lateral palpebral raphe in Caucasians - Lucy Goold (Dove Medical Press, 2009)
Lucy Goold1, Hirohiko Kakizaki1,2,3, Raman Malhotra3, Dinesh Selva11South Australian Institute of Ophthalmology and Discipline of Ophthalmology and Visual Sciences, University of Adelaide, Australia; 2Department of Ophthalmology, Aichi Medical University, Nagakute, Aichi, Japan; 3Corneoplastic Unit and Eye Bank, Queen Victoria Hospital NHS Trust, East Grinstead, West Sussex, United KingdomAbstract: Classical anatomical teaching reports the presence of the lateral palpebral raphe formed at the union in the preseptal and orbital parts of the orbicularis oculi muscle, or by the tendon adhering these to the underlying zygomatic bone. The lateral palpebral raphe has been shown to be absent in Asian cadavers. The current study uses both evidence from the anatomical dissection of five eyelids from three Caucasian cadavers, and histological assessment of the lateral canthus of 13 eyelids from seven Caucasian cadavers to illustrate the absence of the lateral palpebral raphe in Caucasian population.Keywords: lateral palpebral raphe, orbicularis oculi muscle, Caucasian, cadavers